Identity Negotiation of Chinese American’s Twoness in Lisa Ko’s The Leavers: Postcolonial Approach - Eka Nurcahyani; Muhammad Sulthon Kamil (English Department - University of Sultan Ageng Tirtayasa, 2021)
As second-generation Chinese Americans living in the multiracial American society, negotiating their twoness or multicultural identities have been a crucial issue, both in day-to-day life and in postcolonial discourse. This study aims to examine the Chinese American’s twoness identity negotiation as portrayed in The Leavers written by Lisa Ko. To investigate the main character Deming Guo’s process in negotiating his twoness as Chinese American, Bhabha’s postcolonialism theory, Said’s orientalism and Dubois’ concept of twoness are deployed. The findings show that Deming’s identity negotiation was influenced by several important factors, which are family and the society he lived in i.e., the different cultures of parenting and the American community’s prejudices towards Chinese American. It is also revealed that the second-generation Chinese immigrants often mimic and imitate the dominant culture in order to be assimilated with the community. This act of imitation typically generated the feeling of ambivalence when the American culture they adopted clashes with their native Chinese values. They also suffered from racial bias and discrimination from the American community. Nevertheless, Deming ultimately succeeds in negotiating his multicultural identities and settle his twoness by hybridizes his clashing Chinese and American identities. This hybridity creates a balanced identity within him, thus solving his identity ambivalence caused by his twoness